ЕНЕРГЕТИЧНІ ПОКАЗНИКИ АКСІАЛЬНОГО АСИНХРОННОГО ДИСКОВОГО ДВИГУНА ДЛЯ СУДНОВИХ НАВІГАЦІЙНИХ РЛС - Крищук, Р.С.; Гаврилюк, С.І.; Циганкова, Г.А. (Інститут електродинаміки НАН України, Київ, 2021)
The development of a reliable gearless electric drive for antennas of ship radars is an important problem. To solve the problem, this article proposes to use an axial induction motor (AIM) with a massive bimetallic disk-shaped rotor. The AIM model is presented, which consists of three computational domains with the boundary condition of symmetry. To calculate the electromagnetic field, a well-known analytical method of integral transformations is used taking into account the variable along the radial coordinate of the linear speed of the rotor. Ready-to-use expressions are presented for the development of a program for the numerical calculation of the magnetic field and energy characteristics of the motor. Algorithm is developed for calculating the dimensions of the AIM, operating at different speeds with a frequency converter. The numerical calculation program is used to calculate the dimensions AIM. It uses well-known recommendations for the parameters of the electromagnetic field in the magnetic core and in the air gap. The calculation of the dimensions of the AIM for ship radars “Mius” is performed. The dependence of the efficiency on the current frequency for different rotor’s frequencies is investigated. The energy indicators of the AIM are investigated at a variable torque on the shaft and at different rotor speeds. The parameters of the power source for the AIM of ship radars are established. References 20, figures 5, tables 3.